Pharyngeal-cervical-brachial variant of Landry Guillain Barre syndrome after dengue infection: a case report - Sehgal, Vineet; Bhalla, Lucky; Bansal, Priyanshu; Arora, Shaifali (International Journal of Advances in Medicine, 2021)
Dengue is a common mosquito-borne infection in India. We reported a rare Pharyngeal cervical brachial (PCB) variant of Landry Guillain Barre syndrome (LGBS) associated with the dengue virus infection. The pathogenesis seems to be molecular mimicry between gangliosides and microbial lipo-oligosaccharides. PCB usually presents with oropharyngeal or cervicobrachial weakness. Therefore, it must be recognised early and distinguished from conditions presenting with cephalocaudal progressing weakness, such as Myasthenia Gravis, Miller-Fisher syndrome, botulism, diphtheria, porphyria or brain stem stroke. The aim of the study was to add to the limited literature on the PCB variant of LGBS after dengue infection and shed some light on presentation and management options for this rare entity.